Shrinkage and colour in the production of micro-sized PDMS particles for microfluidic applications. (11th April 2018) - Anes, C F; Pinho, D; Muñoz-Sánchez, B N; Vega, E J; Lima, R
Abstract: Polydimethylsiloxane (PDMS), due to its remarkable properties, is a suitable polymer for the production of microparticles with industrial and medical applications. The micro-sized PDMS liquid droplets suffer a pronounced shrinkage while curing to turn into solid particles. In this article, we report the calibration of the shrinkage phenomenon in the production of PDMS microparticles. Our results show that this shrinkage does not depend on the amount of curing agent in the PDMS precursor or on the addition of micro/nanoparticles to the mixture, but on the surface effects due to the relatively large droplet surface-to-volume ratio. Moreover, we have also investigated the addition of colour to the particles to improve their visualization/detection. The addition of colour by using pigments enhances the visualization of the contours of the PDMS microparticles, and reveals the capability of this technique to microencapsulate micro/nanoparticles in PDMS spheres with diameters below 10 μ m. We demonstrate that the technique used in this work is able to work with a wide range of viscosities obtaining an acceptable degree of monodispersity.